Prevalence of depression and associated factors among haemodialysis patients at government and private hospitals in Addis Ababa - Endris, Betelehem; Fikreyesus, Mahelate; Amare, Tadele (African Journal of Nephrology, 2018)
Background: Depression is the most common psychiatric disorder in long-term dialysis patients and a risk factor for morbidity and mortality. Depression in haemodialysis patients has been persistently underdiagnosed and undertreated. There are negative consequences for the individual in respect of family roles, work competence, sexual function and mobility. We aimed to assess the prevalence of depression and associated factors among haemodialysis patients at government and private hospitals in Addis Ababa, Ethiopia. Methods: A cross-sectional study was conducted from May to June 2017 at government and private hospitals in Addis Ababa. The Patient Health Questionnaire (PHQ-9) was used to assess depression and the Oslo Social Support Scale (OSLO-3) was employed to assess social support. Results: A total of 426 patients were included. The mean age was 45.6 ± 15.0 years and 65.3% were male. The prevalence of depression was 60.3%. Factors associated with depression included being female (adjusted odds ratio (OR) 1.7), comorbid medical illness (OR 1.9), poor social support (OR 3.8), and medium income (OR 2.8). Conclusions: Depression is very common among haemodialysis patients in Ethiopia and should always be considered in their management. Being female, having poor social support, being subject to other medical illnesses and a medium level of income were risk factors for depression. Future studies should assess the adequacy of dialysis as under-treatment may contribute to the high rate of depression observed.